Physiological pacing in young patients with complex congenital heart defects. Issue 8 (5th July 2018) - Silvetti, Massimo Stefano; Pazzano, Vincenzo; Battipaglia, Irma; Di Mambro, Corrado; Calvieri, Camilla; Saputo, Fabio Anselmo; Verticelli, Letizia; Carotti, Adriano; Torcinaro, Sergio; Drago, Fabrizio
Abstract: Aim: Young patients with operated complex congenital heart defects (CHD) often develop sinus node dysfunction (SND) requiring permanent pacing with rate‐responsive function. Activity‐driven sensors cannot account for nonmovement stress and cannot modulate heart rate physiologically. Closed Loop Stimulation (CLS, Biotronik, Berlin, Germany) is a physiological rate‐responsive pacemaker based on the indirect measure of ventricular contractility. No data are available on the effects of such pacing strategy in young patients. Methods: We report a series of nine patients with CHD and SND who underwent single‐chamber CLS‐atrial pacing with endocardial or epicardial lead. During the first 30 days, the pacemaker was programmed in AAI pacing mode and then was switched to CLS‐atrial pacing mode. An in‐hospital control was scheduled 1–2 months later to evaluate the CLS response to neurovegetative stresses (i.e., nonmovement stress [Stroop color test, handgrip] and exercise stress test) and Holter monitor. CLS pacing was compared with rate‐responsive accelerometer‐driven pacing (AAIR). Results: At telemetric interrogation, CLS pacing showed a more physiological pattern of 24‐h heart rate trends than accelerometer sensors. The data obtained during nonmovement/exercise stress demonstrated a physiological increase in the pacing rate with CLS, in synergy with spontaneous events. The accelerometer sensor histogram, during nonmovement stress, showed a "nonresponse" behavior (only lower rate events), and during exercise test showed most events in lower rate range. Holter monitoring showed increase of average and maximum heart rate compared with AAIR. Conclusion: In young CHD patients, endocardial/epicardial CLS‐atrial pacing demonstrated a physiological response of heart rate to neurovegetative and physical stresses.